THE INFLUENCE OF CORPORATE GOVERNANCE AND SALES GROWTH ON TAX AVOIDANCE (Empirical Study on cigarette manufacturing sub-sector companies listed on the IDX for the 2018 – 2022 Period) - Audrey Santoso, Jessica; Muid, Dul (Diponegoro Journal of Accounting, 2024)
This research aims to examine the effect of corporate governance and sales growth on tax avoidance. Corporate governance in this research is approximated into three parts, namely institutional ownership, independent board of commissioners, also audit committee. The variables used in this research are dependent variable which consist of tax avoidance, independent variables which consists of institutional ownership, independent board of commissioners, audit committee, also sales growth. This research uses samples from all manufacturing companies in the cigarette sub-sector written on the IDX during the period 2018 - 2022. The sample used in this research is 3 companies that have been selected through purposive sampling and there is 15 samples were obtained. Hypothesis testing in this research uses multiple linear regression analysis using SPSS 22 software. The results of this research show that institutional ownership, independent board of commissioners, also audit committee had no effect on tax avoidance, whereas sales growth had a negative effect on tax avoidance.